The Effectiveness of Drawing Occupation Therapy on the Ability to Control Hallucinations in Schizophrenia: Literature Review - Ibrahim, Masdum; Samiaji, . (KnE Life Sciences, 2021)
Hallucinations are a symptom of mental disorders during which the patient can experience changes in, or receive false messages from, sensory perceptions. Nursing approaches for patients suffering hallucinations are focused on physical, intellectual, emotional and socio-spiritual aspects. One of the therapeutic modalities in the management of schizophrenic patients with hallucinations is occupational therapy, such as drawing activities. The drawing activity aims to minimize the patient’s interaction with their own world; release thoughts, feelings, or emotions that have been affecting the behavior; provide motivation and entertainment; and distract the patient from the hallucinations experienced. The purpose of this study was to summarize the results of studies which explain that occupational drawing therapy can control hallucinations in schizophrenic patients. The research method used is literature review from the search results conducted through Google Scholar. 29 articles were obtained with a combination of the key words including ‘Occupational Therapy’, ‘Drawing’ and ‘Hallucination’ Then the researchers conducted a screening by focusing according to the topic of discussion, so that only 3 articles were obtained that met all the search criteria. The results showed that occupational therapy was effective in controlling hallucinations in schizophrenic patients. It is expected to be a reference in the provision of therapeutic modalities and further research development. Keywords: Schizofrenia, Hallucinations, Occupational Drawing Therapy